Comparison of Effect Size Independent and Disciplined Charcter on Students’ Mathematics Success in Elementary Schools - Manaf, Abdul; Natsir, Siti Rahmalia; Sukmawati, Dina (JME (Journal of Mathematics Education), 2022)
Character values are very important to be instilled in elementary school students. There have been many studies that reveal the value of independent character and discipline related to the success of students' mathematics learning, so this study aims to compare the effect size of the value of independent and disciplined character on the success of learning mathematics at the elementary school level. Types of meta-analysis research. A total of 18 artifacts that were used as data were obtained through a Google Scholar search using predetermined keywords. Data analysis using the help of JASP 0.14.1.0 application. The results of the study obtained an effect size of independent character values (0.43) with a moderate effect category. Effect size discipline character value (0.69) with sufficient effect category. The effect size of the discipline character value is greater than the independent character value. The results of this study have shown that the value of the character of discipline at the elementary school level is more developed and entrenched than the value of independent character. These two character values have a positive and significant relationship in increasing students' success in learning mathematics at the elementary school level.